Severe Psychotic Disorder as the Main Manifestation of Adrenal Insufficiency - Julia de Lima Farah; Carolina Villar Lauand; Lucas Chequi; Enrico Fortunato; Felipe Pasqualino; Luis Henrique Bignotto; Rafael Loch Batista; Ivan Aprahamian (Case Reports in Psychiatry)
We describe a case of severe psychotic disorder as the only manifestation of primary adrenal insufficiency. A 63-year-old man presented with psychotic symptoms without any prior psychiatric history. During the clinical and laboratorial investigation, exams revealed a normovolemic hyponatremia. The patient showed no other clinical signs or symptoms compatible with adrenal insufficiency but displayed very high ACTH and low serum cortisol concentrations. Brain magnetic resonance imaging showed no significant changes, including the pituitary gland. The patient was initially treated with intravenous corticosteroids, resulting in rapid remission of the psychotic symptoms. The association between adrenal insufficiency and neuropsychiatric symptoms is rare but these symptoms can often be the first clinical presentation of the disease.